The mediating effect of diabetes self-management between diabetes self-efficacy and glycemic control among patients with type 2 diabetes (自我管理在2型糖尿病患者自我效能和血糖控制间的中介效应) - CHEN Shanshan (陈闪闪); GUO Hong (郭红); LIN Keke (林可可); WU Shishi (吴诗诗); FANG Jiaxin (方嘉欣) (中西医结合护理)
Objectives To explore the mediating effect of diabetes self-management on the relationship between diabetes self-efficacy and glycemic control among people with type 2 diabetes mellitus (T2DM). Methods By means of convenience sampling, 210 patients with type 2 diabetes were investigated in Beijing Jimenli community health service center using diabetes management self-efficacy scale, diabetes self-management scale, and HbA1c. Results The mean total score of self-efficacy scale for type 2 diabetes patients was( 152. 09±33. 51). The mean total score of the self-management scale was (75. 00±17. 21). The average value of HbA1c was(7. 41±1. 43)%. Self-management was positively correlated with self-efficacy (r=0. 58, P<0. 001) and negatively correlated with HbA 1c (r=-0. 47, P<0. 001). The total effect between self-efficacy and glycemic control was -0. 42(P<0. 001), the direct effect was -0. 21(P<0. 01), and the indirect effect through self-management was -0. 21 (SE=0. 005, Z=-4. 11, P<0. 001). Conclusion The glycemic control level among patients with T2DM was suboptimal. Their self-efficacy level was relatively high but their self-management behaviors are in relatively low level. Self-management partially mediates the relationship between self-efficacy and glycemic control. It is suggested that for those who have low level of self-efficacy, in addition to improving self-efficacy itself, improving self-management would be another way to achieve optimal glycemic control. (目的 探讨2型糖尿病患者自我管理在自我效能与血糖控制之间的作用, 为提高糖尿病患者血糖控制效果提供参考。方法 采用方便抽样的方法, 在北京蓟门里社区卫生服务中心对210例2型糖尿病患者, 使用糖尿病管理自我效能量表、糖尿病患者自我管理量表、糖化血红蛋白(HbA1c)测量值进行问卷调查。结果 2型糖尿病患者自我效能量表总分平均分为(152. 09±33. 51)分, 自我管理量表总分平均分为(75. 00±17. 21)分, HbA1c值平均为(7. 41±1. 43)%。自我管理与自我效能呈正相关(r=0. 58, P＜0. 001)、与HbA1c值呈负相关(r=-0. 47, P＜0. 001); 自我效能与血糖控制之间的总效应为-0. 42(P＜0. 001), 直接效应为-0. 21(P＜0. 01), 通过自我管理的间接效应为-0. 21(SE=0. 005, Z=-4. 11, P<0. 001)。结论 2型糖尿病患者血糖控制效果不佳, 自我效能水平较高, 自我管理能力较低。自我管理在自我效能和血糖控制之间存在部分中介效应。建议医务工作者在采取提高糖尿病患者血糖控制效果的干预措施时, 一方面可以通过提高患者的自我效能, 直接提高血糖控制效果; 另一方面可通过提高患者自我管理水平的策略来间接提高患者的血糖控制效果。)